Therapeutic Effects of Vanillic Acid on Acetaminophen-Induced - Deepa Mol, Sathyaneson (International Journal of Pharmaceutical & Biological Archive, 2010)
Acetaminophen is a widely used analgesic and antipyretic drug. An overdose can cause life-threatening hepatotoxicity and nephrotoxicity, in humans and experimental animals. In this study the potential protective role of vanillic acid one of the major phenolic derivatives from edible plants and fruits was evaluated against the acetaminophen (APAP) induced toxicity in rats. Toxicity was induced in adult male albino rats, weighing 140–160 g, by an intraperitoneal injection of APAP (750 mg/kg body weight) for 7 days. Rats were treated with vanillic acid (100 mg/kg body weight) by oral administration. APAP intoxicated rats showed significantly increase in the levels of renal function markers such as urea, uric acid and creatinine in serum. Further, increased levels of total cholesterol, triglycerides, free fatty acids (FFA), LDL (low density lipoproteins), VLDL (very low density lipoproteins) and decreased HDL (high density lipoproteins) in plasma and tissues such as liver and kidney were observed in APAP intoxicated rats when compared to control. These parameters were reversed after the treatment with vanillic acid. Histopathological findings of vanillic acid against APAP rat’s kidney confirmed the biochemical findings of this study. In conclusion, vanillic acid administration significantly decreased the level of renal function markers and showed beneficial effects on lipid profile in APAP rats.